Knowledge, attitudes and practice in relation to noise-induced hearing loss in two factories - Balachandar, S.S.; Anselm, T.S.; David, K. (2014)
There has been a global increase in prevalence of occupational noise-induced hearing loss. The aim of this study is to explore' mean score levels on knowledge, attitude and practice regarding noise-inducedhearing loss among participants of the two factories and also to determine the frequency of distribution of health education. In this intervention study, there were 203 participants from the two factories in the automobile industry. The sample size required was 23 in each factory. A questionnaire about knowledge, attitude and practice regarding noise-induced hearing loss questionnaires was distributed among the participants. The results revealed that there were no differences in mean scores on knowledge, belief, feelings, judgment and practice among participants from the two factories. However, the health education intervention elicited statistically significant changes in mean score of knowledge over time, F (1.44, 289.45) = 13.54, P < 0.001, partial 112= 0.063; mean score of belief subdomain (attitude) over time, F (1.71,344.17) = 7.78, p = 0.00 I, partial 112'= 0.037 and mean score of practice over time, F (1.49, 300.16) = 9.46, p < 0.00 I, partial 112= 0.045, the mean score levels reduced over six months compared to the first month. This study concludes the knowledge, belief and practice constructs towards noise-induced hearing loss had improved over a period of six months, but there were no differences in the outcomes between participants from the two factories. Hence, regular employee health education, at least six monthly is required in a hearing conservation program.